Correction to: A Cross-Systematic Review of Addressing Risks in Building Information Modelling-Enabled International Construction Projects - Ganbat, Tsenguun; Chong, Heap-Yih; Liao, Pin-Chao; Lee, Cen-Ying (Archives of computational methods in engineering, 2021)
In the paper (A Cross-Systematic Review of Addressing Risks in Building Information Modelling-Enabled International Construction Projects, Tsenguun Ganbat, Heap-Yih Chong, Pin-Chao Liao, Cen-Ying Lee) which appeared in “Archives of Computational Methods in Engineering”, the authors state that in the published Acknowledgements section one of the funding numbers is not correct. The corrected Acknowledgements section appears below.